Antireflection film, optical element, optical system, and imaging device
Patent Information
- Application Number
- JP2022041285
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-03-16
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing antireflection films suffer from low adhesion between layers, leading to potential peeling and insufficient mechanical strength, environmental durability, and stain resistance.
A multilayer antireflection film structure comprising magnesium fluoride, silicon oxide, and a fluorine-containing organic compound layers, with specific refractive index and thickness ratios to enhance adhesion and durability.
The multilayer film structure provides improved mechanical strength, environmental durability, and stain resistance by offsetting stress between layers and ensuring robust adhesion.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical field
[0001] The present invention relates to an optical element, an optical system, and an optical instrument. [Background technology]
[0002] Patent Document 1 describes MgF 2 An antireflection film is disclosed that includes an antifouling layer made of a fluorine-containing organic compound on the outermost surface of the antireflection film. Patent Document 2 discloses that MgF on the outermost surface 2 SiO is deposited on the surface of the layer using a vacuum evaporation method. 2 An antireflection film is disclosed in which a layer is formed and an antifouling film made of a fluororesin is provided on the surface of the film. [Prior art documents] [Patent document]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 2009-92746 [Patent Document 2] International Publication No. 2013 / 118622 [Summary of the invention] [Problem to be solved by the invention]
[0004] In the structure of the antireflection film disclosed in Patent Document 1, MgF 2 The adhesion between the layer and the antifouling layer is low, and there is a possibility that the film will peel off. In the structure of the antireflection film disclosed in Patent Document 2, MgF 2 Since the layer has high tensile stress, SiO 2 Adhesion to the layer is low, and film peeling may occur. Therefore, the configuration of the antireflection film disclosed in Patent Document 1 or Patent Document 2 cannot provide an optical element with high mechanical strength, environmental durability, and stain resistance.
[0005] Therefore, an object of the present invention is to provide an optical element with high mechanical strength, environmental durability, and antifouling properties. [Means to solve the problem]
[0006] An optical element as one aspect of the present invention is an optical element having a base material and an antireflection film, wherein the antireflection film includes a first film formed on the base material, and a first film formed on the base material. and a second film formed on the film, and the second film consists of the first layer, the second layer, and the third layer in order from the side closest to the first film. The first layer contains magnesium fluoride, the second layer contains silicon oxide and aluminum oxide, and the third layer contains a fluorine-containing organic compound.
[0007] Other objects and features of the invention are illustrated in the following examples.
Effect of the invention
[0008] According to the present invention, it is possible to provide an optical element with high mechanical strength, environmental durability, and stain resistance. [Brief explanation of the drawing]
[0009]
Figure 1
Figure 2
[0010] Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings.
[0011] First, with reference to FIG. 1, the schematic configuration of the optical element 300 in Examples 1 to 8 will be described. FIG. 1 is a schematic cross-sectional view showing an optical element 300. The optical element 300 includes a substrate (base material) 200 and an antireflection film 100 formed on the substrate 200. The substrate 200 is, for example, a transparent substrate made of a resin material or a glass material. The antireflection film 100 is composed of a multilayer film (first film) 111 and a multilayer film (second film) 101 in order from the substrate 200. That is, the antireflection film 100 includes a multilayer film 111 formed on the substrate 200 and a multilayer film 101 formed on the multilayer film 111 (formed farthest from the substrate 200).
[0012] Multilayer film 111 consists of layers 11, 12, 13, 14, 15, and 16 in order from the side closest to substrate 200. Note that in this embodiment, the multilayer film 111 consists of six layers, but is not limited to this. The number of layers in the multilayer film 111 may be any number as long as it is one or more. The multilayer film 101 consists of three layers, in order from the side closest to the multilayer film 111: layer (first layer) 01, layer (second layer), and layer 03.
[0013] Layer 01 is magnesium fluoride (MgF 2 )including. Layer 02 is silicon oxide (SiO 2 ) and aluminum oxide (Al 2 O 3 ). It is known that silicon oxide materials containing trace amounts of aluminum form denser films upon vapor deposition than materials that do not contain aluminum. Therefore, layer 02 becomes a strong film with excellent scratch resistance and has very large compressive stress. Layer 03, which is the outermost layer of antireflection film 100, contains a fluorine-containing organic compound and has excellent water and oil repellency. Therefore, if water droplets or dirt adhere to the layer 03, the water droplets or dirt can be easily removed.
[0014] Layer 02 and layer 03 are strongly adhered to each other by chemically bonding silicon oxide and fluorine-containing organic compound contained in each layer. On the other hand, layer 01 containing magnesium fluoride has large tensile stress. By bringing the layer 01 having tensile stress and the layer 02 having compressive stress close to each other, the respective stresses are offset, and the adhesion between the layers 01 and 02 can be improved. By forming the multilayer film 101 as described above, the adhesion of the film is increased and the scratch resistance is improved.
[0015] In Examples 1 to 8, the refractive index at the d-line of layers 01, 02, and 03 was set to n 1 ,n 2 ,n 3 , the physical thickness of layers 01, 02, and 03 is d 1 ,d 2 ,d 3 (nm) and the wavelength of the d-line is λ, it is preferable that the following conditional expression (1) be satisfied.
[0016] λ / 8≦n 1 d 1 +n 2 d 2 +n 3 d 3 ≦λ / 2 …(1) More preferably, the numerical range of conditional expression (1) is set as shown in conditional expression (1a) below.
[0017] λ / 6≦n 1 d 1 +n 2 d 2 +n 3 d 3 ≦λ / 3 …(1a) When the outermost layer (top layer) of the antireflection film 100 is made of a material with a lower refractive index and the optical film thickness is set to about λ / 4, the antireflection performance is improved. In Examples 1 to 8, the antireflection performance can be improved by regarding the multilayer film 101 as a layer substantially equivalent to the low refractive index material of the outermost layer and satisfying conditional expression (1).
[0018] Further, in Examples 1 to 8, it is preferable that the following conditional expression (2) is satisfied.
[0019] 0.2≦n 1 d 1 / (n 1 d 1 +n 2 d 2)≦0.9 …(2) More preferably, the numerical range of conditional expression (2) is set as shown in conditional expression (2a) below.
[0020] 0.6≦n 1 d 1 / (n 1 d 1 +n 2 d 2 )≦0.9 …(2a) When the thickness of layer 01 of multilayer film 101 is increased, the average refractive index of multilayer film 101 decreases, but the increase in tensile stress makes it difficult to ensure adhesion. On the other hand, if the thickness of the layer 02 is increased, the tensile stress decreases and adhesion can be easily ensured, but the average refractive index of the multilayer film 101 increases. By forming each film so that its thickness satisfies conditional expression (2), it is possible to achieve both antireflection performance and adhesion.
[0021] When the substrate 200 is made of a resin material, heating causes deformation and cracking. Therefore, the antireflection film 100 needs to be formed without heating (or by heating at a low temperature of 80° C. or lower). Magnesium fluoride deposited without heating (or by heating at a low temperature of 80°C or less) has a low film strength. Additionally, resin materials generally have a larger coefficient of thermal expansion than glass. Since the substrate 200 itself tends to expand, forming a film with a large compressive stress on the substrate 200 makes it more difficult for film cracking and film peeling to occur. In view of the above two points, it is preferable to have a structure in which the magnesium fluoride layer is sandwiched between layers containing a silicon oxide material containing a trace amount of aluminum.
[0022] Further, in Examples 1 to 8, it is preferable that the following conditional expression (3) is satisfied.
[0023] 1.4≦n 2 ≦1.5…(3) Further, in Examples 1 to 8, layer 02 preferably contains silicon oxide in a weight ratio of 90% or more. Also preferably, layer 02 contains aluminum oxide at a weight ratio of 10% or less. Even a silicon oxide film containing aluminum oxide at a weight ratio of 0.001% can prevent film cracking and film peeling when combined with a magnesium fluoride film. Furthermore, since the multilayer film 101 is a layer equivalent to the outermost low refractive index material layer, when the refractive index becomes 1.5 or more, the antireflection performance decreases.
[0024] Next, with reference to FIG. 2, the schematic configuration of the optical element 301 in Examples 9 to 12 will be described. FIG. 2 is a schematic cross-sectional view showing the optical element 301. The optical element 301 includes a substrate (base material) 200 and an antireflection film 110 formed on the substrate 200. The antireflection film 110 is composed of a multilayer film (first film) 111 and a multilayer film (second film) 101 in order from the substrate 200. That is, the antireflection film 100 includes a multilayer film 111 formed on the substrate 200 and a multilayer film 101 formed on the multilayer film 111 (formed farthest from the substrate 200).
[0025] The multilayer film 101 includes, in order from the side closest to the multilayer film 111, layer (first layer) 02-1, layer (second layer) 01, layer (third layer) 02-2, and layer (fourth layer). Consists of 3 layers (layer) 03. Layer 02-1 contains silicon oxide and a trace amount of aluminum (aluminum oxide). Layer 01 contains magnesium fluoride. Layer 02-2 contains silicon oxide and a trace amount of aluminum (aluminum oxide). Layer 03 contains a fluorine-containing organic compound.
[0026] In Examples 9 to 12, the refractive index at the d-line of layers 02-1, 01, 02-2, and 03 was 2-1 ,n 1 ,n 2-2 ,n 3 , the physical thickness of layers 02-1, 01, 02-2, and 03 is d, respectively. 2-1 ,d 1 ,d 2 ,d 3 (nm), and the wavelength of the d-line is λ. At this time, it is preferable that the following conditional expression (4) be satisfied.
[0027] λ / 8≦n 2-1 d 2-1 +n 1 d 1 +n 2-2 d 2-2 +n 3 d 3 ≦λ / 2 …(4) More preferably, the numerical range of conditional expression (4) is set as shown in conditional expression (4a) below.
[0028] λ / 6≦n 2-1 d 2-1 +n 1 d 1 +n 2-2 d 2-2 +n 3 d 3 ≦λ / 3 …(4a) Further, in this embodiment, it is preferable that the following conditional expressions (5) and (6) are satisfied.
[0029] 0.2≦n 1 d 1 / (n 2-1 d 2-1 +n 1 d 1 +n 2-2 d 2-2 )≦0.9 …(5) 0.5≦n 2-1 d 2-1 / n 2-2 d 2-2 ≦2.0…(6) More preferably, the numerical ranges of conditional expressions (5) and (6) are set as shown in conditional expressions (5a) and (6a) below.
[0030] 0.4≦n 1 d 1 / (n 2-1 d 2-1 +n 1 d 1 +n 2-2 d 2-2 )≦0.8 …(5a) 0.8≦n 2-1 d 2-1 / n 2-2 d 2-2 ≦1.2 …(6a) According to Examples 9 to 12, strength can be improved by sandwiching layer 01 containing magnesium fluoride between layers 02-1 and 02-2 containing silicon oxide and a trace amount of aluminum (aluminum oxide). I can do it. Further, by applying compressive stress to the antireflection film 110, the stress of the substrate 200 can be offset.
[0031] Further, in Examples 9 to 12, it is preferable that the following conditional expressions (7) and (8) be satisfied.
[0032] 1.4≦n 2-1 ≦1.5…(7) 1.4≦n 2-2 ≦1.5…(8) Further, in Examples 9 to 12, layer 02-1 and layer 02-2 preferably contain silicon oxide in a weight ratio of 90% or more. Also preferably, layer 02-1 and layer 02-2 contain aluminum oxide in a weight ratio of 10% or less. Even a very small amount of aluminum is effective. Even a silicon oxide film containing aluminum oxide at a weight ratio of 0.001% can prevent film cracking and film peeling when combined with a magnesium fluoride film. Furthermore, since the multilayer film 101 is a layer equivalent to the outermost low refractive index material layer, when the refractive index becomes 1.5 or more, the antireflection performance decreases.
[0033] In the optical elements 300 and 301, the film thickness d of layer 03 made of a fluorine-containing organic compound 3 preferably satisfies the following conditional expression (9).
[0034] 2≦d 3 ≦10…(9) This is because if the film thickness is too thin, the water repellent and antifouling effects will be reduced, and the surface will become cloudy, impairing its functionality.
[0035] In the optical elements 300 and 301, as the material for layer 03, halogenated silane compounds such as dimethyldichlorosilane, diethyldichlorosilane, and diphenylvinyldichlorosilane, or alkoxysilane compounds such as dimethyldiethoxysilane can be used. Furthermore, as the material for layer 03, an aminosilane compound such as bis(dimethylamino)methylsilane or hexamethylsidylazane, or a fluorine-containing aminosilane compound may be used. These fluorine-containing organic compounds are not particularly limited as long as they can impart functions such as water repellency, oil repellency, and dust resistance.
[0036] The multilayer film 111 is a combination of a high refractive index material and a medium refractive index material (with a refractive index of about 1.6 to 1.8 at the d-line), or a combination of high refractive index materials and low refractive index materials (alternating layers). layer) is preferable. When the substrate 200 is made of a resin material, it is more preferable to have alternating layers of high refractive index material and low refractive index material. Since the resin material is easily expanded by heat, it is preferable that the low refractive index material is the same material as the layer 02 which has a large compressive stress. On the other hand, when the substrate 200 is made of a glass material, from the viewpoint of preventing white stains, it is preferable that the layer 11 of the multilayer film 111 is made of a material containing aluminum oxide as a main component. The high refractive index material is preferably a material whose main component is tantalum oxide, titanium oxide, lanthanum oxide, or zirconia oxide, or a mixture of a plurality of these.
[0037] The method for forming the multilayer film 111 and the antireflection film 100 (or antireflection film 110) made of the multilayer film 101 is not particularly limited, as long as it is a physical vapor deposition method such as a vapor deposition method, a sputtering method, or an ion plating method. It's not something you can do. In particular, the vapor deposition method is more preferable because fluoride is difficult to decompose. In the vapor deposition method, methods for heating the vapor deposition material include a resistance heating method, an electron beam vapor deposition method, a laser vapor deposition method, and the like. The electron beam evaporation method is more preferable because the film material can be directly heated, the film can be formed on the substrate 200 without heating, there is less contamination, and the quality of the film is relatively high. It is also preferable to use an ion beam assist method. By using an independent ion source to assist in vapor deposition, a dense film with low absorption and scattering and high strength can be formed.
[0038] Each example will be specifically described below.
Example
[0039] FIG. 1 is a schematic cross-sectional view of an optical element 300 in Example 1. The optical element 300 of this embodiment is an optical element in which an antireflection film 100 is formed on a substrate 200. The substrate 200 is S-BSL7 (manufactured by OHARA) with a refractive index of 1.52 (d-line). The layer material is SiO 2 (Al weight ratio 4.5%), MgF 2 , Ta 2 O 5 , and Al 2 O 3 is used. As the fluorine-containing organic compound, OF-SR (manufactured by Canon Optron) is used. Table 1 shows details of the film structure of the optical element of this example. The refractive index and film thickness of each material satisfy equations (1), (2), (3), and (9).
[0040] The method for forming the antireflection film 100 of this example is as follows. The antireflection film 100 is formed by a vapor deposition method. The inside of the vacuum chamber of the evaporation equipment is 2×10 -3 It is evacuated to a high vacuum area near (Pa). The film forming temperature for each layer of the multilayer film 111 and layers 01 and 02 of the multilayer film 101 is 200° C., and an electron beam evaporation method is used. In addition, in order to form a denser film, ion beam assisted vapor deposition is performed. After confirming that the inside of the vacuum chamber is in a high vacuum state, Ar is introduced as an inert gas into the ion gun, and the ion gun is discharged. After the ion gun is in a stable state, oxygen is introduced into the vacuum chamber and the vacuum pressure is 1×10 -2 Perform ion-assisted deposition using oxygen ions at about (Pa). For layer 03 of the multilayer film 101, the film formation temperature was 80° C., and a resistance heating evaporation method was used. After the film formation is completed, excess OF-SR is removed by wiping the surface of the optical element 300 taken out with ethanol.
[0041] FIG. 3 shows the reflectance characteristics of the optical element in this example. In FIG. 3, the horizontal axis represents wavelength (nm), and the vertical axis represents reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.3% or less, which is a very good property.
[0042] Layer 01 made of magnesium fluoride has strong tensile stress. On the other hand, the layer 02 made of silicon oxide containing 4.5% aluminum by weight is strong and has compressive stress. By arranging layer 02 having strong compressive stress on top of layer 01 having strong tensile stress, these stresses are offset. As a result, the antireflection film 100 is a film that does not cause cracks or peeling and has excellent environmental reliability.
[0043] In order to confirm the durability of the antireflection film 100 under various conditions, the following durability test was conducted. (High temperature and high humidity storage test) After the prepared sample was left in a constant temperature bath set at a temperature of 60 degrees and a humidity of 90% for 1000 hours, the appearance of the antireflection film 100 was visually observed. (Low temperature storage test) After the prepared sample was left in a constant temperature bath set at -30 degrees for 1000 hours, the appearance of the antireflection film 100 was visually observed. (High temperature storage test) After the prepared sample was left in a constant temperature bath set at 70 degrees for 12 hours, the appearance of the antireflection film 100 was visually observed. (Adhesion test) After applying an adhesive tape to the surface of the anti-reflection film 100 of the prepared sample, the tape is peeled off in a direction perpendicular to the film surface. The test was repeated 5 times and visually observed to see if the film had peeled off. (Surface hardness test) After rubbing the antireflection film 10 times with a solvent-dipped Silbon paper under a load of about 200 g, the appearance of the antireflection film 100 was visually observed.
[0044] Table 13 shows the results of the durability test. In both tests, it can be confirmed that no film cracking or peeling occurred, and that a good antireflection film was formed.
[0045]
table 1
Example
[0046] In the optical element 300 of Example 2, the substrate 200 is S-BSM14 (manufactured by OHARA) with a refractive index of 1.60 (d-line). Further, the optical element 300 of this example is manufactured using the same vapor deposition material and the same vapor deposition conditions as in Example 1. Table 2 shows details of the film structure of the optical element of this example. The refractive index and film thickness of each material satisfy equations (1), (2), (3), and (9). FIG. 4 shows the reflectance characteristics of the optical element in this example. In FIG. 4, the horizontal axis represents wavelength (nm), and the vertical axis represents reflectance (%). The reflectance is 0.25% or less in the wavelength range of 420 to 680 nm, which is a very good property.
[0047] Table 13 shows the results of the durability test. In both tests, it can be confirmed that no film cracking or peeling occurred, and that a good antireflection film was formed.
[0048] [Table 2]
Example
[0049] In the optical element 300 of Example 3, the substrate 200 is S-BAH32 (manufactured by OHARA) with a refractive index of 1.67 (d-line). The layer material is SiO containing 4.5% Al by weight. 2 , Ta 2 O 5 , MgF 2 is used. As the fluorine-containing organic compound, OF-SR (manufactured by Canon Optron) is used. The optical element 300 of this example was manufactured under the same vapor deposition conditions as in Example 1. Table 3 shows details of the film structure of the optical element of this example. The refractive index and film thickness of each material satisfy equations (1), (2), (3), and (9). FIG. 5 shows the reflectance characteristics of the optical element in this example. In FIG. 5, the horizontal axis represents wavelength (nm), and the vertical axis represents reflectance (%). The reflectance is 0.25% or less in the wavelength range of 420 to 680 nm, which is a very good characteristic.
[0050] Table 13 shows the results of the durability test. In both tests, it can be confirmed that no film cracking or peeling occurred, and that a good antireflection film was formed.
[0051] [Table 3]
Example
[0052] In the optical element 300 of Example 4, the substrate 200 is S-LAH66 (manufactured by OHARA) with a refractive index of 1.77 (d-line). The optical element 300 of this example is manufactured using the same vapor deposition material as in Example 3 and the same vapor deposition conditions as in Example 1. Table 4 shows details of the film structure of the optical element of this example. The refractive index and film thickness of each material satisfy equations (1), (2), (3), and (9). FIG. 6 shows the reflectance characteristics of the optical element in this example. In FIG. 6, the horizontal axis represents wavelength (nm), and the vertical axis represents reflectance (%). The reflectance is 0.2% or less in the wavelength range of 420 to 680 nm, which is a very good property.
[0053] Table 13 shows the results of the durability test. In both tests, it can be confirmed that no film cracking or peeling occurred, and that a good antireflection film was formed.
[0054] [Table 4]
Example
[0055] In the optical element 300 of Example 5, the substrate 200 is S-TIH53 (manufactured by OHARA) with a refractive index of 1.85 (d line). The optical element 300 of this example is manufactured using the same vapor deposition material as in Example 4 and the same vapor deposition conditions as in Example 1. Table 5 shows details of the film structure of the optical element of this example. The refractive index and film thickness of each material satisfy equations (1), (2), (3), and (9). FIG. 7 shows the reflectance characteristics of the optical element in this example. In FIG. 7, the horizontal axis represents wavelength (nm), and the vertical axis represents reflectance (%). The reflectance is 0.3% or less in the wavelength range of 420 to 720 nm, which is a very good property.
[0056] Table 13 shows the results of the durability test. In both tests, it can be confirmed that no film cracking or peeling occurred, and that a good antireflection film was formed.
[0057] [Table 5]
Example
[0058] In the optical element 300 of Example 6, the substrate 200 is S-NPH3 (manufactured by OHARA) with a refractive index of 1.96 (d line). The optical element 300 of this example was manufactured using the same vapor deposition material as in Example 4 and the same vapor deposition conditions as in Example 1. Table 6 shows details of the film structure of the optical element of this example. The refractive index and film thickness of each material satisfy equations (1), (2), (3), and (9). FIG. 8 shows the reflectance characteristics of the optical element in this example. In FIG. 8, the horizontal axis represents wavelength (nm), and the vertical axis represents reflectance (%). The reflectance is 0.4% or less in the wavelength range of 420 to 720 nm, which is a very good characteristic.
[0059] Table 13 shows the results of the durability test. In both tests, it can be confirmed that no film cracking or peeling occurred, and that a good antireflection film was formed.
[0060] [Table 6]
Example
[0061] In the optical element 300 of Example 7, the substrate 200 is S-LAH79 (manufactured by OHARA) with a refractive index of 2.00 (d-line). The optical element 300 of this example was manufactured using the same vapor deposition material as in Example 4 and the same vapor deposition conditions as in Example 1. Table 7 shows details of the film structure of the optical element of this example. The refractive index and film thickness of each material satisfy equations (1), (2), (3), and (9). FIG. 9 shows the reflectance characteristics of the optical element in this example. In FIG. 9, the horizontal axis represents wavelength (nm), and the vertical axis represents reflectance (%). The reflectance is 0.3% or less in the wavelength range of 420 to 720 nm, which is a very good property.
[0062] Table 13 shows the results of the durability test. In both tests, it can be confirmed that no film cracking or peeling occurred, and that a good antireflection film was formed.
[0063] [Table 7]
Example
[0064] In the optical element 300 of Example 8, the substrate 200 is fluorite with a refractive index of 1.43 (d-line). The layer material is SiO containing 4.5% Al by weight. 2 ,Ti 2 O 3 and Ta 2 O 5 mixture of MgF 2 is used. As the fluorine-containing organic compound, OF-SR (manufactured by Canon Optron) is used. When fluorite is rapidly cooled, cracks occur. Therefore, the antireflection film 100 is entirely deposited without heating. The optical element 300 of this example was manufactured under the same vacuum degree and ion assist conditions as in Example 1. SiO containing 4.5% Al by weight 2 , Ti 2 O 3 and Ta 2 O 5 mixture of MgF 2 uses ion-assisted deposition to increase strength. Table 8 shows details of the film structure of the optical element of this example. The refractive index and film thickness of each material satisfy equations (1), (2), (3), and (9). FIG. 10 shows the reflectance characteristics of the optical element in this example. In FIG. 10, the horizontal axis represents wavelength (nm), and the vertical axis represents reflectance (%). The reflectance is 0.2% or less in the wavelength range of 420 to 680 nm, which is a very good characteristic.
[0065] Table 13 shows the results of the durability test. In both tests, it can be confirmed that no film cracking or peeling occurred, and that a good antireflection film was formed.
[0066] [Table 8]
Example
[0067] The optical element 300 of Example 9 is an optical element in which an antireflection film 110 is formed on a substrate 200. The substrate 200 is E48R (manufactured by Zeon Corporation) with a refractive index of 1.53 (d line). The layer material is SiO containing 4.5% Al by weight. 2 , Ti 2 O 3 and Ta 2 O 5 mixture of MgF 2 is used. As the fluorine-containing organic compound, OF-SR (manufactured by Canon Optron) is used. E48R (substrate 200), which is a resin material, deforms when exposed to high temperatures. Therefore, the antireflection film 100 is entirely vapor-deposited without heating. The optical element 300 of this example was manufactured under the same vacuum degree and ion assist conditions as in Example 1. SiO containing 4.5% Al by weight 2 , Ti 2 O 3 and Ta 2 O 5 mixture of MgF 2 uses ion-assisted deposition to increase strength. Table 9 shows details of the film structure of the optical element of this example. The refractive index and film thickness of each material satisfy equations (4), (5), (6), (7), (8), and (9). FIG. 11 shows the reflectance characteristics of the optical element in this example. In FIG. 11, the horizontal axis represents wavelength (nm), and the vertical axis represents reflectance (%). The reflectance is 0.2% or less in the wavelength range of 420 to 680 nm, which is a very good characteristic.
[0068] Table 13 shows the results of the durability test. In both tests, it can be confirmed that no film cracking or peeling occurred, and that a good antireflection film was formed.
[0069] [Table 9]
Example
[0070] In the optical element 301 of Example 10, the substrate 200 is EP-5000 (manufactured by Mitsui Gas Chemical Co., Ltd.) with a refractive index of 1.64 (d-line). The optical element 301 of this example was manufactured using the same vapor deposition material and the same vapor deposition conditions as in Example 9. Table 10 shows details of the film structure of the optical element of this example. The refractive index and film thickness of each material satisfy equations (4), (5), (6), (7), (8), and (9). FIG. 12 shows the reflectance characteristics of the optical element in this example. In FIG. 12, the horizontal axis represents wavelength (nm), and the vertical axis represents reflectance (%). The reflectance is 0.2% or less in the wavelength range of 420 to 680 nm, which is a very good characteristic.
[0071] Table 13 shows the results of the durability test. In both tests, it can be confirmed that no film cracking or peeling occurred, and that a good antireflection film was formed.
[0072] [Table 10]
Example
[0073] In the optical element 301 of Example 11, the substrate 200 is E48R (manufactured by Zeon Corporation) with a refractive index of 1.53 (d line). The optical element 301 of this example is manufactured using the same vapor deposition material and the same vapor deposition conditions as in Example 11. Table 11 shows details of the film structure of the optical element of this example. The refractive index and film thickness of each material satisfy equations (4), (5), (6), (7), (8), and (9). FIG. 13 shows the reflectance characteristics of the optical element in this example. In FIG. 13, the horizontal axis represents wavelength (nm), and the vertical axis represents reflectance (%). The reflectance is 0.4% or less in the wavelength range of 420 to 760 nm, which is a very good property.
[0074] Table 13 shows the results of the durability test. In both tests, it can be confirmed that no film cracking or peeling occurred, and that a good antireflection film was formed.
[0075] [Table 11]
Example
[0076] In the optical element 301 of Example 12, the substrate 200 is EP-5000 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) with a refractive index of 1.64 (d-line). The optical element 301 of this example was manufactured using the same vapor deposition material and the same vapor deposition conditions as in Example 9. Table 12 shows details of the film structure of the optical element of this example. The refractive index and film thickness of each material satisfy equations (4), (5), (6), (7), (8), and (9). FIG. 14 shows the reflectance characteristics of the optical element in this example. In FIG. 14, the horizontal axis represents wavelength (nm), and the vertical axis represents reflectance (%). The reflectance is 0.4% or less in the wavelength range of 420 to 760 nm, which is a very good property.
[0077] Table 13 shows the results of the durability test. In both tests, it can be confirmed that no film cracking or peeling occurred, and that a good antireflection film was formed.
[0078] [Table 12]
[0079] [Table 13]
Example
[0080] Next, the optical system in Example 13 will be described with reference to FIG. 15. FIG. 15 is a cross-sectional view of optical system 400. Optical system 400 includes a plurality of optical elements G401 to G411. 402 is an aperture, and 403 is an imaging plane. F412 is a filter placed on the object side of the optical system 400.
[0081] Each of the optical elements G401 to G411 is a lens. Of these lenses, the antireflection coating of any one of Examples 1 to 12 is applied to at least one of the entrance surface and the exit surface. That is, the plurality of optical elements G401 to G411 are the optical elements 300 on which the antireflection film 100 of any one of Examples 1 to 8 is formed, or the optical element 300 on which the antireflection film 110 of any one of Examples 9 to 12 is formed. Includes element 301.
[0082] The R1 surface of optical element G401 and the R2 surface of optical element G411 are the outermost surfaces of optical system 400. It is preferable to apply an antireflection film 100 or an antireflection film 110 to the R1 surface and the R2 surface because dirt and the like easily adhere thereto. Filter F412 is an element that is disposed closer to the object than optical element G401 and can be removed depending on the intended use. Therefore, it is preferable to apply the antireflection film 100 or the antireflection film 110 to the R3 surface and the R4 surface of the filter F412, since dirt and the like are likely to adhere thereto.
[0083] Note that the optical system 400 of this embodiment is not limited to an imaging optical system used in an imaging device to be described later, but can be applied to optical systems for various uses such as binoculars, projectors, and telescopes.
Example
[0084] Next, referring to FIG. 16, an imaging device in Example 14 will be described. FIG. 16 is an external perspective view of the imaging device (digital camera 500).
[0085] The digital camera 500 includes a camera body 502 and a lens device 501 that is integrally configured with the camera body 502. However, the present embodiment is not limited to this, and the lens device 501 may be an interchangeable lens that can be attached to and detached from the camera body 502, such as for a single-lens reflex camera or a mirrorless camera. In this case, FIG. 16 corresponds to a state in which the lens device 501 is attached to the camera body 502. The lens device 501 includes, for example, the optical system 400 of Example 13. The camera body 502 has an image sensor 503 such as a CMOS sensor or a CCD sensor. The image sensor 503 is arranged on the imaging plane 403 of the optical system 400.
[0086] According to each example, it is possible to provide an optical element, an optical system, and an optical device that have high mechanical strength, environmental durability, and antifouling properties.
[0087] Although preferred embodiments of the present invention have been described above, the present invention is not limited to these embodiments, and various modifications and changes can be made within the scope of the invention. [Explanation of symbols]
[0088] 100 Anti-reflection coating 101 Multilayer film (second film) 111 Multilayer film (first film) 200 Substrate (base material) 300 optical elements
Claims
1. An anti-reflective coating formed on an optical surface of a substrate, comprising: the antireflection film comprises a first film formed on the optical surface and a second film formed on the first film, the second film includes, in order from the side closest to the first film, a first layer, a second layer, and a third layer; the first layer comprises magnesium fluoride; the second layer comprises silicon oxide and aluminum oxide; The anti-reflective coating, wherein the third layer contains a fluorine-containing organic compound.
2. The refractive index of the first layer at the d line is n 1 The refractive index of the second layer at the d line is n 2 The refractive index of the third layer at the d line is n 3 , the physical thickness of the first layer is d 1 (nm), the physical thickness of the second layer is d 2 (nm), the physical thickness of the third layer is d 3 (nm) and the wavelength of the d-line is λ (nm), λ / 8≦n 1 D 1 +n 2 D 2 +n 3 D 3 ≦λ / 2 2. The anti-reflection coating according to claim 1, which satisfies the following condition:
3. λ / 6≦n 1 D 1 +n 2 D 2 +n 3 D 3 ≦λ / 3 3. The anti-reflection coating according to claim 2, which satisfies the following condition:
4. The refractive index of the first layer at the d line is n 1 The refractive index of the second layer at the d line is n 2 , the physical thickness of the first layer is d 1 (nm), the physical thickness of the second layer is d 2 (nm), 0.2≦n 1 d 1 / (n 1 d 1 +n 2 d 2 )≦0.9 4. The anti-reflection film according to claim 1, which satisfies the following condition:
5. 0.6≦n 1 d 1 / (n 1 d 1 +n 2 d 2 )≦0.9 5. The anti-reflection coating according to claim 4, which satisfies the following condition:
6. The refractive index of the second layer at the d line is n 2 When 1.4≦n 2 ≦1.5 6. The anti-reflection film according to claim 1, which satisfies the following condition:
7. 7. The anti-reflection coating according to claim 1, wherein the second layer contains 90% or more silicon oxide by weight.
8. 8. The anti-reflection coating according to claim 1, wherein the second layer contains aluminum oxide in an amount of 10% or less by weight.
9. An anti-reflective coating formed on an optical surface of a substrate, comprising: the antireflection film comprises a first film formed on the optical surface and a second film formed on the first film, the second film includes, in order from the side closest to the first film, a first layer, a second layer, a third layer, and a fourth layer; the first layer and the third layer include silicon oxide and aluminum oxide; the second layer comprises magnesium fluoride; The fourth layer comprises a fluorine-containing organic compound.
10. The refractive index of the first layer at the d line is n 2-1 The refractive index of the second layer at the d line is n 1 The refractive index of the third layer at the d line is n 2-2 The refractive index of the fourth layer at the d line is n 3 , the physical thickness of the first layer is d 2-1 (nm), the physical thickness of the second layer is d 1 (nm), the physical thickness of the third layer is d 2-2 (nm), the physical thickness of the fourth layer is d 3 (nm) and the wavelength of the d-line is λ (nm), λ / 8≦n 2-1 D 2-1 +n 1 D 1 +n 2-2 D 2-2 +n 3 D 3 ≦λ / 2 10. The anti-reflection coating according to claim 9, which satisfies the following condition:
11. λ / 6≦n 2-1 D 2-1 +n 1 D 1 +n 2-2 D 2-2 +n 3 D 3 ≦λ / 3 11. The anti-reflection coating according to claim 10, which satisfies the following condition:
12. The refractive index of the first layer at the d line is n 2-1 The refractive index of the second layer at the d line is n 1 The refractive index of the third layer at the d line is n 2-2 The refractive index of the fourth layer at the d line is n 3 , the physical thickness of the first layer is d 2-1 (nm), the physical thickness of the second layer is d 1 (nm), the physical thickness of the third layer is d 2-2 (nm), the physical thickness of the fourth layer is d 3 (nm) and the wavelength of the d-line is λ (nm), 0.2≦n 1 d 1 / (n 2-1 d 2-1 +n 1 d 1 +n 2-2 d 2-2 )≦0.9 0.5≦n 2-1 d 2-1 / n 2-2 d 2-2 ≦2.0 12. The anti-reflection film according to claim 9, which satisfies the following condition:
13. 0.4≦n 1 d 1 / (n 2-1 d 2-1 +n 1 d 1 +n 2-2 d 2-2 )≦0.8 0.8≦n 2-1 d 2-1 / n 2-2 d 2-2 ≦1.2 13. The anti-reflection coating according to claim 12, which satisfies the following condition:
14. The refractive index of the first layer at the d line is n 2-1 The refractive index of the third layer at the d line is n 2-2 When 1.4≦n 2-1 ≦1.5 1.4≦n 2-2 ≦1.5 14. The anti-reflection film according to claim 9, which satisfies the following condition:
15. 15. The anti-reflection coating according to claim 9, wherein the first layer and the third layer each contain silicon oxide at a weight ratio of 90% or more.
16. 16. The anti-reflection coating according to claim 9, wherein the first layer and the third layer each contain aluminum oxide at a weight ratio of 10% or less.
17. An anti-reflective film according to any one of claims 1 to 16, An optical element comprising the substrate.
18. An optical system having a plurality of optical elements including the optical element described in claim 17.
19. The optical element according to claim 17, and an imaging element that receives light from the optical element.
